FREQUENCY OF REMISSION AFTER TREATMENT WITH HYPER CVAD PROTOCOL IN NEWLY DIAGNOSED PATIENTS OF ACUTE LYMPHOBLASTIC LEUKEMIA PRESENTING TO JINNAH HOSPITAL LAHORE - Muhammad Kashif; Tahir Mehmood; Kausar Bano et al. (Journal of University Medical & Dental College, 2019)
ABSTRACT: OBJECTIVE: The objective of this study was to determine the frequency of complete and partial remission after 2 courses of hyper CVAD regimen in newly diagnosed patients of acute lymphoblastic leukemia (ALL). MATERIAL AND METHODS: This study was conducted on 100 patients of ALL presenting to the oncology department of Jinnah Hospital, Lahore and fulﬁlling the inclusion criteria from 01-012016 to 30-12-2016. Patients were undergone treatment with hyper CVAD regimen according to the standard protocol. Complete or partial remission rate was checked after 2 session of hyper CVAD regimen. CT scan (chest and abdomen) was performed for conﬁrmation of extramedullary disease. RESULTS: The mean age of study population was 35.68 ± 8.69 years. There were 48% male patients while female patients were 52%. Complete remission was present in 72% patients. Partial remission was present in 24% patients. There was no signiﬁcant association between complete remission and age (p-value=0.497). No signiﬁcant association was found between partial remission and age (p-value=0.103). Signiﬁcant association was found between partial remission and complete remission with gender having p-value=0.001 and 0.01 respectively. CONCLUSION: The frequency of complete and partial remission after 2 courses of hyper CVAD regimen in newly diagnosed patients of ALL was 72% and 24% respectively. Eﬀect modiﬁers have no signiﬁcant inﬂuence except gender.